Emerging Role of Carbon Ion Radiotherapy in Reirradiation of Recurrent Head and Neck Cancers: What Have We Achieved So Far? - Bhattacharyya, Tapesh; Koto, Masashi; Windisch, Paul; Ikawa, Hiroaki; Hagiwara, Yasuhito; Tsuji, Hiroshi; Adeberg, Sebastian (Frontiers in Oncology, 2022)
Abstract: Administering reirradiation for the treatment of recurrent head and neck cancer is extremely challenging. These tumors are hypoxic, radioresistant, and need escalated radiation dose to get adequately controlled. The obstacle to delivering this escalated dose of radiation to the target is their proximity to critical organs at risk and possible development of consequent severe late toxicities. With the emergence of highly sophisticated technologies, Intensity Modulated Radiotherapy (IMRT) and Stereotactic Body Radiotherapy (SBRT) have shown promising outcomes in this setting. Proton beam radiotherapy (PBRT) has already been used in locally recurrent head and neck cancers because of its excellent physical dose distribution exploring sharp Bragg peak properties with negligible entrance and exit dose. To further improve these results Carbon ion radiotherapy (CIRT) has been explored in few countries of Europe and Asia because of its favorable physical properties with minimal entrance and exit dose, sharper lateral penumbra, and much higher and variable relative biological effectiveness which is not possible to achieve with any other forms of radiation at the moment. There are very few studies describing the role of CIRT in recurrent head and neck cancer published in the literature. In this article, we are discussing the different aspects of carbon ion in reirradiation of recurrent head and neck cancers including European and Asian experiences, different dose schedules, dose constraints of OARs, outcomes, and toxicities, and a brief comparison with proton beam and IMRT.